Comparative mitogenomics analysis of Peltigera species and new insights into the lichen phylogenetics - Mamut, Reyim; Yisilam, Gulbar; Adil, Guldiyar; Anwar, Gulmira (Frontiers in Microbiology, 2025)
The genus Peltigera includes terricolous and muscicolous foliose macrolichens that are common and widespread across the majority of continents. The genus is well-defined by the absence of a lower cortex and the presence of a dense arachnoid-tomentose pilema that usually bears anastomosing pale or dark veins with numerous solitary or confluent rhizines. However, the high morphological similarity among its species poses significant taxonomic challenges for accurate identification, often necessitating the use of molecular data. This study presents a comprehensive mitogenomic analysis of 11 Peltigera species, with the aim of elucidating their genetic structure and taxonomic status. We sequenced and performed de novo assembly of the complete mitochondrial genomes, followed by comprehensive genomic analysis. This analysis revealed that the circular genome length ranged in length from 52,107 bp to 76,353 bp with guanine and cytosine (GC) contents between 26.4 and 27.4%. The mitogenomes encoded 15 protein-coding genes (PCGs), 26–27 transfer RNAs (tRNAs), and 2 ribosomal RNAs (rRNAs). Our analysis revealed a variety of scattered repeats, simple repeats, and tandem repeats, predominantly in intergenic and intron regions. Additionally, we examined codon usage and conducted a synteny analysis within the mitogenomes of Peltigera species. These findings enhance our understanding of the genetic evolution and phylogenetic relationships within Peltigera, providing a scientific foundation for future research on the diversity and evolution of lichenized fungi.